Kinetic e ffect of using stories in the development of creative thinking for kindergarten kidsAfaf - Abdullah , Afaf; Faisal, Ghada (Journal of Physical Education, 2023)
The researchers with her experiences and masters ideas declare the research problem which is the kindergarten popular activity which surrounded with classical cover in the contents specialist in physical education , that will not enable the way to the children to development there ability creative ,there is the question about the activity of small games and movieng stories to development there ability creative ,therefore The researchers setup an educational program include some of motor stories which include some of sport games then knowing the effect of these stories on the research sample .